Chemical Education and Research in Europe, Part I - Silverman, Alexander (1928)
This silent film is the first of two captured by American chemist Alexander Silverman during a tour of university chemistry departments and laboratories across Europe in 1928-1929. His edited footage contains title cards in English introducing each new location. Silverman's travels include Berlin, Germany (Friedrich Wilhelm University, Kaiser Wilhelm Institute for Chemistry); several locations in Italy (Universities of Rome, Florence, Bologna, and Padua); Munich, Germany (Adolf von Bayer Memorial, Laboratory of Pure and Applied Chemistry, statues of Max Joseph von Pettenkofer and Justus Liebig); the University of Jena; the Czech Republic (Joachimsthal/Jáchymov, the Street of the Alchemists in Prague); Oxford, England (laboratory of Frederick Soddy, Radcliffe Science Library, William Henry Perkin's laboratory), and London, England (National Physical Laboratory, Davy Faraday Laboratory, and The Royal Institute).
Keywords: Max-Planck-Institut für Chemie (Otto-Hahn-Institut); Chemical laboratories; Universität Bonn; Università di Roma; Università di Firenze; Università di Bologna; Università di Padova; Czech Republic--Jáchymov; University of Oxford; National Physical Laboratory (Great Britain); Royal Institute of Chemistry